Delayed Cardiac Tamponade following Open Heart Surgery - Kanzaki, Yoshio; Kohno, Satoshi; Imai, Katsuhiko; Komiya, Tatsuhiko; Kohchi, Kazuhiro; Shiraga, Kohtaro (Japanese Journal of Cardiovascular Surgery, 1995)
Twenty-two cases with delayed cardiac tamponade following open cardiac surgery were divided into three groups according to the color and hematocrit value of pericardial fluid. In 7 patients (group B) more than half of pericardial fluid consisted of the patient's blood (mean hematocrit 31%), in 9 patients (group D) there was less blood (mean hematocrit 8%), and in 6 patients (group E) it was serous. In group B, compared with group E, the patients had more often received postoperative anticoagulant therapy (100% vs 37%, p<0.05), more often developed excess anticoagulation (thrombo test<15%) (71% vs 17%, p<0.05), and had undergone longer cardiopulmonary bypass (260±74 vs 194±49min, p<0.05). Postoperative anticoagulant therapy seems to be a risk for delayed cardiac tamponade due to intrapericardial bleeding.